2013
DOI: 10.5455/medarh.2013.67.410-413
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pharmacologic Treatment of Patients with Low Back Pain Treated at Kosovo Energetic Corporation

Abstract: Introduction:Low back pain (LBP) is a common complaint among the general population with a subgroup developing chronic and disabling symptoms generating large societal costs. Recurrences and functional limitations can be minimized with appropriate conservative management, including medications, physical therapy modalities, exercise and patient education.Objectives:The purpose of this study was to determine the prevalence of low back complaints in industrial workers, to investigate whether individual risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A great number of studies have demonstrated that absolute rest is inefficient for the chronic non-specific low back pain 6) as well as taking drugs for the pain, since they only achieve short-term benefits. Although there is no evidence of medium and long-term benefits, it is a well-known fact that drugs cause undesirable effects on the organism 7,8) . Other therapies such as thermotherapy and electrotherapy with transcutaneous electrical nerve stimulation or interferential stream have proved to be ineffective as well [9][10][11] .…”
mentioning
confidence: 99%
“…A great number of studies have demonstrated that absolute rest is inefficient for the chronic non-specific low back pain 6) as well as taking drugs for the pain, since they only achieve short-term benefits. Although there is no evidence of medium and long-term benefits, it is a well-known fact that drugs cause undesirable effects on the organism 7,8) . Other therapies such as thermotherapy and electrotherapy with transcutaneous electrical nerve stimulation or interferential stream have proved to be ineffective as well [9][10][11] .…”
mentioning
confidence: 99%
“…One systematic review including 51 randomized controlled trials comparing NSAIDs with placebo found strong evidence that NSAIDs significantly improved pain control . Additionally, 3 small randomized clinical trials identified by systematic review found no significant difference in symptoms or return to work when opioid analgesics, acetaminophen, and NSAIDs were compared …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported possitive or negative association between computer use and musculosceletal symptoms ( 24 - 26 ). The prevalence of Computer Carpal Syndrome (CTS) among computer professionals based on clinical signs and sympoms is approximately 13,1% and almost 1 out of every computer professional suffers from this condition.…”
Section: Discussion and Reccomendations On Therapeutic Modalitiesmentioning
confidence: 99%
“…Aydan Oral et al Had written paper about Evidence Based Physical Medicine and Rehabilitation strategies for patients with cervical radiculopathy due to disc herniation. They reported that neck pain affected 4,82% of the world population in 2010, ranks second after low back pain among musculoskeletal disorders as one of the leading causes of years lived with disability, with contribution of 33,6 million years ( 26 ). Physical medicine and rehabilitation interventions in radicular neck pain and their evidence based are: a) educational interventions; b) exercise; c) workplace interventions/ergonomics; d) phyasical agents (TENS, therapeutic ultrasound, low-level laser therapy) pulsed electromagnetic field therapy, non-invasive brain stimulation techniques, etc); e) injection therapy (epidural steroids, botulinum toxin, ozone); f) cervical collars; g) traction; manual therapies (massage, manipulation and mobilization (commonly used in the management of discogenic neck pain); complementary and alternative medicine treatments (acupuncture, herbal medicine, etc.).…”
Section: Discussion and Reccomendations On Therapeutic Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation